Unpacking resilience: exploring the link between dissociative responses and psychological resilience in war-affected Palestinians - Yacoub, Hamzeh; Sabbah, Suheir S.; Yacoub, Zaid; Yacoub, Rita; Sabbah, Khalil; Yasin, Diana; Ghannam, Yousef B. (Frontiers in Psychiatry, 2025)
IntroductionPeritraumatic dissociation (PD) is a psychological response to trauma involving disruptions in awareness, memory, and identity. While PD is associated with adverse outcomes such as PTSD, the role of resilience in shaping dissociative experiences remains underexplored, particularly in conflict-affected populations.ObjectiveTo examine the relationship between peritraumatic dissociation and psychological resilience among Palestinians exposed to war-related trauma.MethodsA cross-sectional survey was conducted among 623 Palestinian participants from Gaza, the West Bank, and Israeli-controlled areas during the December 2024 Gaza-Israel war. Peritraumatic dissociation was assessed using the Peritraumatic Dissociative Experiences Questionnaire (PDEQ), and resilience was measured using the 10-item Connor-Davidson Resilience Scale (CD-RISC-10). Linear and multiple linear regression analyses were used to assess relationships and predictors.ResultsParticipants demonstrated moderate levels of both PD (M=28.31, SD=8.44) and resilience (M=32.38, SD=8.92). Regression analysis revealed a significant positive association between resilience and PD (β=0.404, p < 0.001). Females reported significantly higher PD levels than males, while higher education was associated with greater resilience. A history of mental illness predicted both higher dissociation and lower resilience.ConclusionContrary to expectations, resilience was positively correlated with peritraumatic dissociation, suggesting a complex relationship between psychological endurance and acute dissociative responses. Rather than indicating an adaptive role for dissociation, the findings may reflect the intensity of trauma exposure among resilient individuals in conflict zones.